Entrepreneurship as an Occupational Choice - Gaweł , Aleksandra (Research Papers in Economics and Finance, 2022)
This article aims to consider the entrepreneurship as an occupational choice and to understand the flow among different forms of occupations. The choice of the form of professional activity depends on the perception of attractiveness of both forms,  people who perceive entrepreneurial profits as more beneficial than workers’ wages more likely decide to become entrepreneurs than waged employees. However, in the presented paper, the choice is considered not only between entrepreneurship and employment but also concerns the scale of entrepreneurship. The issue of entrepreneurship as an occupational choice is presented empirically using the time series data for Poland on a quarterly basis in the years 2003-2018. The influence of the overall economic situation, which determines business opportunities and average salaries, on the choice between a proper entrepreneur, a quasi-entrepreneur and a hired worker is presented with the use of regression analysis. The results show that changes in the overall economic situation and in the level of average wages lead to flows between proper entrepreneurs and quasi-entrepreneurs, and thus, to changes in the employment structure. Improving market conditions encourage people to follow the path of proper entrepreneurship or to become hired workers, while abandoning quasi-entrepreneurship.